Azide-based heterobifunctional poly(ethylene oxide)s: NaN3-initiated "living" polymerization of ethylene oxide and chain end functionalizations. Issue 2 (10th November 2015) - Yang, Sera; Kim, Youn; Kim, Hyeong Cheol; Siddique, Abu B.; Youn, Gyusaang; Kim, Hyun Jun; Park, Hyeon Jong; Lee, Jae Yeol; Kim, Sehoon; Kim, Jungahn
Abstract : Sodium azide (NaN3 )-initiated "living" ring-opening polymerization of ethylene oxide and chain end functionalizations. Abstract : In this study, sodium azide (NaN3 ) was employed as a functional anionic initiator to polymerize ethylene oxide in N, N -dimethylformamide (DMF) leading to the production of the reactive polymeric alkoxide. The molecular weights of all products were controlled within the 2800–10 000 g mol −1 range on the basis of the stoichiometric balance. NaN3 -initiated polymerization of ethylene oxide (EO) and chain end functionalization of the resulting alkoxide were found to be a simple and efficient method for synthesizing heterobifunctional PEOs. The reaction route via chain end tosylation of α-azide PEOs was found to yield almost quantitative functionalizations for the synthesis of α-azide-ω-tosyl PEO, α-azide-ω-thiol PEO, and α-amine-ω-thiol PEO (over 98 mol%).